1992
DOI: 10.1007/bf00178469
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and co-localization of immunoreactive helospectin with vasoactive intestinal polypeptide and peptide histidine methionine in human nasal mucosa, soft palate and larynx

Abstract: Regulatory peptide immunoreactivities reported in the upper respiratory system of man include vasoactive intestinal polypeptide (VIP) and peptide histidine methionine (PHM), which are co-localized in a network of fine varicose nerve fibers. The present study was undertaken to examine the possible occurrence and distribution of the recently described VIP-like peptide helospectin. Double immunofluorescence labelling showed that helospectin is co-localized with VIP and PHM. In addition to nerve fibers containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
3
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
3
3
1
Order By: Relevance
“…33 Nerve fibers with VIP-Li have been shown to originate from neurons in the sphenopalatine and pterygopalatine ganglia, 1,34,35 and, in common with many NANC neurotransmitters, VIP often co-localizes with other neurotransmitters, including nitric oxide, helospectin, peptide histidine methionine, and acetylcholine. 8,5,35 Nevertheless, the identification of fibers with VIPLi in the nasal mucosa of all species studied to date 5,7,36 is at variance with our findings in horses. The apparent absence or low expression of VIP in nasal mucosal nerve fibers of horses was an unexpected finding, because in other species, innervation with VIP-containing fibers has an important role in nasal mucosal function.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…33 Nerve fibers with VIP-Li have been shown to originate from neurons in the sphenopalatine and pterygopalatine ganglia, 1,34,35 and, in common with many NANC neurotransmitters, VIP often co-localizes with other neurotransmitters, including nitric oxide, helospectin, peptide histidine methionine, and acetylcholine. 8,5,35 Nevertheless, the identification of fibers with VIPLi in the nasal mucosa of all species studied to date 5,7,36 is at variance with our findings in horses. The apparent absence or low expression of VIP in nasal mucosal nerve fibers of horses was an unexpected finding, because in other species, innervation with VIP-containing fibers has an important role in nasal mucosal function.…”
Section: Discussioncontrasting
confidence: 84%
“…[1][2][3][4][5][6][7] A variety of other NANC neurotransmitters (eg, peptide histidine isoleucine, peptide histidine methionine, helospectin, gastrin-releasing peptide, galanin, and nitric oxide) have also been identified in mammalian nasal mucosa. 4,[8][9][10][11][12][13][14][15] Many of these neurotransmitters co-localize with each other or with noradrenaline and acetylcholine, resulting in an extremely complex innervation pattern. Along with the classic cholinergic and adrenergic innervation, all of the NANC neurotransmitters are believed to be involved in control and maintenance of nasal mucosal function, 16 and it is hypothesized that alterations in nasal innervation play a role in the etiopathogenesis of disease.…”
mentioning
confidence: 99%
“…Only few to moderate number of VIP positive neuronal structures were observed in alveolar process mucosa; a moderate number of nerves was found in the soft and hard palate and vomer mucosa of our patients. However, numerous VIP immunoreactive nerve fibres have been found in healthy human soft palate mucosa [35]. Similarly to our findings, VIP positive nerve fibres have been found in the wall of blood vessels in healthy human mucosa and in the subepithelium of healthy rat hard palate [31,35].…”
Section: Discussionsupporting
confidence: 87%
“…It is assumed that cystic distension of the glands and increased permeability of the small blood vessels may be more or less involved in the growth of nasal polyps [2], Several investigators have demonstrated a consider able number of autonomic nerve fibers such as cholinergic and adrenergic fibers and various neurotransmitters in the nasal mucosa [3][4][5][6][7][8], These neurotransmitters may play a specific role in the regulation of blood flow and gland activation in normal and diseased nasal mucosa [9]. Although some studies delineate the anatomical distri bution of neurotransmitters and neurohormones in nor mal nasal mucosa of several species including man [10,11], an immunohistochemical study on nasal polyps is still lacking.…”
Section: Introductionmentioning
confidence: 99%